Linguistic and ontological challenges of multiple domains contributing to transformed health ecosystems - Kreuzthaler, Markus; Brochhausen, Mathias; Zayas, Cilia; Blobel, Bernd; Schulz, Stefan (Frontiers in Medicine, 2023)
This paper provides an overview of current linguistic and ontological challenges which have to be met in order to provide full support to health ecosystems transforming in order to meet precision medicine standards. It highlights both, standardization and interoperability aspects regarding formal, controlled representations of clinical and research data, requirements for smart support to produce and encode content in a way that machines and humans can understand and process it. Starting from the linguistic practices common in the medical and research community, it addresses the state of the art in processing of medical language by computers, for instance using natural language processing (NLP). An additional key aspect of the linguistic perspective of managing health information and data is the integration of heterogeneous data sources, employing different formal ontologies or different languages. This is the area where biomedical ontologies come into play. The paper discusses the state of the art regarding biomedical ontologies and addresses their standardization effect. Finally, the paper points out the next and possible synergies of both NLP and biomedical ontologies to foster interoperability of data for precision medicine.